2020
DOI: 10.52571/ptq.v17.n35.2020.45_al-jaberi_pgs_536_548.pdf
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Analytic Method for Solving Linear and Non-Linear Telegraph Equation

Abstract: The modeling of many phenomena in various fields such as mathematics, physics, chemistry, engineering, biology, and astronomy is done by the nonlinear partial differential equations (PDE). The hyperbolic telegraph equation is one of them, where it describes the vibrations of structures (e.g., buildings, beams, and machines) and are the basis for fundamental equations of atomic physics. There are several analytical and numerical methods are used to solve the telegraph equation. An analytical solution considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this section, we introduce the basic definitions and properties of fractional calculus [21][22][23][24]. Definition 1.…”
Section: Basic Definitions Of Fractional Calculusmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we introduce the basic definitions and properties of fractional calculus [21][22][23][24]. Definition 1.…”
Section: Basic Definitions Of Fractional Calculusmentioning
confidence: 99%
“…Recently, many authors have studied different inequalities of Riemann-Liouville fractional integrals; for more details, see [21][22][23][24]. Some properties of the operator j α , which are needed here, are as follows:…”
Section: Basic Definitions Of Fractional Calculusmentioning
confidence: 99%
“…In this article, the author has extended the implementation of a new analytical technique, which is named the fractional novel analytical method (FNAM). This method FNAM was developed by Araya Wiwatwanich [43][44][45] and was used for the solutions of higher nonlinear fractional partial differential equations. In the present work, it is observed that the results obtained by FNAM are quite excellent as compared to other analytical techniques.…”
Section: Introductionmentioning
confidence: 99%